Efektivitas Fungsi Tuha Peut Gampong dalam Pembahasan Anggaran Pendapatan dan Belanja Gampong (APBG) - Afzalul Ridha; Nur Sari Dewi. M (Constitutional Law and Siyasah Department, Sharia and Law Faculty, IAIN, 2022)
Tuha Peut in Gampong Juli Meunasah Tambo was still not optimal in carrying out his functions during the discussion of the Gampong Revenue and Expenditure Budget. This is due to a lack of understanding of the main tasks and functions of tuha peut during the discussion, so they only supervise and give approval to the RAPBG, such as the discussion of Gampong Qanun Number 2 of 2021 concerning the Gampong Juli Meunasah Tambo Expenditure Budget for the 2021 fiscal year. empirical juridical research. The results of the study show that the function of Tuha Peut has not been implemented effectively. During the discussion of the gampong income and expenditure budget, Tuha Peut gampong tends to assume that this function has been carried out only with the representative of the Tuha Peut chairman. As for the inhibiting factors for Tuha Peut in carrying out their functions, namely internal and external factors from the Tuha Peut themselves